Repair bond strength of bulk-fill composites: influence of different primers and direction of debonding stress - Ahlholm Pekka; Staxrud Frode; Sipilä Kirsi; Vallittu Pekka (Taylor & Francis, 2025)
The purpose of this in vitro study was to evaluate the effect of different adhesion primers on the repair bond strength of bulk-fill resin composite and short-term hydrolytic stability of the repair interface before and after accelerated aging. In addition, direction of debonding stress was examined. Bulk-fill substrates were aged in water for 14 days at 37 °C. Smooth resin composite surfaces were prepared for the substrates with a superfine grinding paper (FEPA \#500, \#1200, \#2000). Test specimens were produced by attaching bulk-fill composite to the substrate surfaces, using three different primer/bonding systems. Specimens were aged 24 h at 37 °C in water, or thermal cycled (5–55 °C/5,000 cycles). Subsequently, shear bond strength and micro-tensile bond strength were evaluated. In total there were 60 specimens for the shear bond strength and 60 specimens for the micro-tensile bond strength measurements (30 stored in water 24 h, 30 thermal cycled, n = 10 in each primer/bonding mode). The mean shear bond strength was 9.1–13.1 MPa after 24 h water storage and 6.9–10.7 MPa after thermal cycling. The mean micro-tensile bond strength was 28.7–45.8 MPa after 24 h water storage and 22.7–37.9 MPa after thermal cycling. The Ceramic primer (silane containing) seems to perform better than the three-step etch and rinse adhesive or the Composite primer. Shear-type stress had an adverse effect on the repair bond strength of bulk-fill resin composites.